2013
DOI: 10.1128/ec.00238-12
|View full text |Cite
|
Sign up to set email alerts
|

Improved Gene Ontology Annotation for Biofilm Formation, Filamentous Growth, and Phenotypic Switching in Candida albicans

Abstract: The opportunistic fungal pathogen Candida albicans is a significant medical threat, especially for immunocompromised patients. Experimental research has focused on specific areas of C. albicans biology, with the goal of understanding the multiple factors that contribute to its pathogenic potential. Some of these factors include cell adhesion, invasive or filamentous growth, and the formation of drug-resistant biofilms. The Gene Ontology (GO) (www.geneontology.org) is a standardized vocabulary that the Candida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The work on biofilm and filamentous growth in Candida (28), heart development (29), a case study of focused curation for renal and cardiovascular research (30) and in depth curation of the peroxisome proteome in humans (31) will be instructive for learning about curation of the literature to create GO annotations.…”
Section: Suggested Readingmentioning
confidence: 99%
“…The work on biofilm and filamentous growth in Candida (28), heart development (29), a case study of focused curation for renal and cardiovascular research (30) and in depth curation of the peroxisome proteome in humans (31) will be instructive for learning about curation of the literature to create GO annotations.…”
Section: Suggested Readingmentioning
confidence: 99%
“…For instance, genes and compounds that control morphogenesis often also control biofilm development (Giacometti et al 2011;Du et al 2012b;Tsang et al 2012;Connolly et al 2013;Fazly et al 2013). Not surprisingly, 68 out of the 122 genes that are involved in biofilm formation are also involved in filamentous growth in C. albicans (Inglis et al 2012). Some of these factors, such as Ras1, Cyr1/Cdc35, and Efg1, regulate Candida biofilm formation, filamentous growth, phenotypic switching, and pathogenesis (Inglis et al 2012).…”
Section: Morphogenesis In Community Developmentmentioning
confidence: 99%
“…Not surprisingly, 68 out of the 122 genes that are involved in biofilm formation are also involved in filamentous growth in C. albicans (Inglis et al 2012). Some of these factors, such as Ras1, Cyr1/Cdc35, and Efg1, regulate Candida biofilm formation, filamentous growth, phenotypic switching, and pathogenesis (Inglis et al 2012). In Cryptococcus, Znf2, the decision maker of the yeast to hypha transition and the mediator of the cryptococcal ability to cause disease, regulates more than half of the potential adhesins encoded in the genome LWang and X Lin, unpubl.).…”
Section: Morphogenesis In Community Developmentmentioning
confidence: 99%
“…albicans adhesion and growth are particularly necessary for biofilm formation (Inglis et al, 2013;Silva et al, 2011). Our study showed that CSC significantly increased C. albicans adhesion and growth and promoted biofilm formation.…”
Section: Effect Of Tobacco Tar On Biofilm and Germ Tube Formation Of mentioning
confidence: 99%